Determinación del índice de vulnerabilidad sísmica de las viviendas de Ciudad Bolívar evaluadas por el método cualitativo - Muñoz Prieto, William (Revista Científica, 2006)
Next I present the results of a research project named Analysis of Housing Vulnerability Seismic in the Ciudad Bolivar District and its possible solutions according to qualitative method, in order to determine the vulnerability seis index in the rubblework buildings. This project was carry out in some districts of Ciudad Bolivar. With the auspice of The Universidad Distrital Francisco José de Caldas. To develop this research a sample in 300 housings was taken, the studied population was taken from different districts on 19 locality, the visited section permitted to know the housing construction characteristics which can be the answers or the reaction in front of a nature event. The preliniinary facts permit to select a specific sample from 100 housings which got represent the structure kind and the constructions present in the housings in the study population as a shallow geological formation in which are settled. The methodology used in developing this Project was a qualitative method, proposed by the Engineering Seismic Association (ESA), from the adaptation of the the specifics characteristics saw. Taking into account this procedure and the analysis of the most important aspects and the housing vulnerability of these 100 houses, was designed a procedure simplifying to evaluate the vulnerability grade in the houses of the studied population. As a result of this study it was determined that the 76% of the housings from the studied population are extremely vulnerable and that 56 from them can represent a risk for the people, even before that occurs a strong seismic by the instability of the structural elements and the no structural element with serious failures that affect thé behavior and the functionalism of these housings. Besides the study showed that the sitüation. of the Ciudad Bolivar housings presents a higher risk. In 100 houses they were identified 37 extremely vulnerable. Also it was identified that the level of damages saw and the vulnerability seismic in the evaluated houses are connected with the bad structural and construction quality_ and.the progressive rdamage óf the structural and no structural elements.